Pengaruh Desain Interior dan Menu Makanan Terhadap Peningkatan Jumlah Pengunjung Sobat Coffee di Kota Solok - Niken Sriwahyuni; Ida Nirwana; Wahyu Indah Mursalini (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of interior design and food menu on increasing the number of visitors to Solok's Coffee Buddy. This study uses a quantitative approach. The data was processed using hypothesis analysis with validity test models, reliability tests, multiple linear regression, t-test, f-test, and determination. The data used are primary data with 60 questionnaires. Data collection is done that is sourced directly from the respondents. Based on the analysis that has been done, it is obtained that Y = 9,110 + 0,117 X1 + 0,644 X2 + e and the T test is obtained 0, 909 and 5,090 which means that the Interior Design variable has no significant effect on the increase in the number of visitors, and the food menu has a significant effect on the increase. Number of visitors. Judging from the R (Square) value of 0.350, which means that Interior Design and Food Menus have an effect of 35% on the increase in the number of visitors, and the increase in the number of visitors to Sobat Coffee, Solok City is influenced by other variables of 65% which were not examined in this study. From the analysis of the F test, the Fcount value is 20,686 > Ftable 3,11, which means that the Interior Design and Food Menu variables have a significant and simultaneous effect on the increase in the number of visitors.